Crystal structure of Ca5Nb5O17 - Guevarra, Jonathan (Animo Repository, 2005)
The crystal structure of Ca5Nb5O17, an n=5 member of the homologous series AnBnO3n+2, at room temperature has been determined by single-crystal X-ray diffraction using synchrotron radiation with a CCD area detector. The structure is monoclinic with spacegroup P21/c (b unique) and lattice parameters a=7.7494(3) Å, b=5.4928(1) Å, c=32.241(1) Å, and β=96.809(4)∘. It consists of perovskite-like slabs of corner-sharing NbO6 octahedra separated by an interslab region, where the octahedra on opposite sides of the gap do not share oxygen atoms resulting in an extra layer of oxygen atoms with respect to the ideal perovskite structure. The slabs are five octahedra wide. Ca atoms within the slabs occupy 12-fold coordinated sites whereas those at the borders show irregular coordination environments. The distortion of the octahedra increases from the center to the borders of the slabs. The computed valences for the Nb ions are very close to 5 at the borders while smaller values were obtained for sites in the middle of the slabs which suggests that the electrical conduction takes place predominantly in the middle of the slabs